2004
DOI: 10.1152/ajpgi.00206.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin regulates the heparin-binding epidermal-like growth factor promoter via a PKC/EGFR-dependent mechanism

Abstract: Gastrin is a known growth/differentiation factor for the gastric mucosa. Its effects are likely mediated by the induction of heparin-binding epidermal-like growth factor (HB-EGF), a member of the EGF family of growth factors that is expressed by gastric parietal cells. In this study, we investigated the regulation of the HB-EGF promoter by gastrin in a human gastric cancer cell line. Serial human HB-EGF promoter-luciferase reporter deletion constructs and heterologous promoter constructs were transfected into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…It has been previously reported that H. pylori can induce an up-regulation in both HB-EGF gene expression and ectodomain shedding in human gastric cells (35,36). In addition, it has been shown that gastrin stimulation results in the up-regulation of the HB-EGF gene in gastric cells transfected with CCK-2R (37). We speculated that the presence of CCK-2R might render gastric cells more susceptible to H. pylori-induced HB-EGF gene and protein up-regulation.…”
Section: Resultsmentioning
confidence: 97%
“…It has been previously reported that H. pylori can induce an up-regulation in both HB-EGF gene expression and ectodomain shedding in human gastric cells (35,36). In addition, it has been shown that gastrin stimulation results in the up-regulation of the HB-EGF gene in gastric cells transfected with CCK-2R (37). We speculated that the presence of CCK-2R might render gastric cells more susceptible to H. pylori-induced HB-EGF gene and protein up-regulation.…”
Section: Resultsmentioning
confidence: 97%
“…This mechanism involves transactivation of the epidermal growth factor (EGF) receptor. In gastric epithelial cells, gastrin induces the expression and processing of proHB-EGF leading to the release of HB-EGF, tyrosine phosphorylation of EGF receptors and the subsequent activation of downstream signaling pathways (327,475). In contrast, gastrin induces EGF receptor transactivation in intestinal cells via an intracellular signaling pathway mediated by Src family kinases (191).…”
Section: Mitogen-activated Kinase Cascadesmentioning
confidence: 99%
“…In these cells, the mechanism by which CCK2R induces HB-EGF gene transcription involves activation of PKCs and the EGF receptor and requires a GC-rich region of the promoter (475).…”
Section: Target Genes Of Cholecystokinin Receptors a Gastrin-depementioning
confidence: 99%
“…Importantly, much emphasis has been placed on the ability of gastrin to both up-regulate ligands of the epidermal growth factor (EGF) receptor, in particular amphiregulin and heparin-binding EGF-like growth factor (HB-EGF; refs. [16][17][18]. The effect of gastrin on both the shedding of EGF receptor growth factors and related downstream signaling pathways has received particular attention.…”
Section: Introductionmentioning
confidence: 99%